Bacillus spp. and Pisolithus tinctorius effects on Quercus ilex ssp. ballota: a study on tree growth, rhizosphere community structure and mycorrhizal infection - Domenech, Jezabel; Ramos-Solano, Beatriz; Probanza, Agustin; Lucas-Garcı́a, José Antonio; Colón, Juan José; Gutiérrez-Mañero, Francisco Javier (Forest Ecology and Management, 2004)
A local species of oak (Quercus ilex ssp. ballota) was inoculated or co-inoculated with the ectomycorrhizal fungus Pisolithus tinctorius and two plant growth promoting rhizobacteria (PGPR) of the genus Bacillus (Bacillus licheniformis CECT 5106 and Bacillus pumilus CECT 5105). Effects of inoculation on growth, on N acquisition by the plant roots, changes in rhizosphere microbial communities and the degree of mycorrhization were evaluated. Only B. licheniformis promoted the growth of Q. ilex seedlings while co-inoculation of either bacterial strain with P. tinctorius had a negative effect on plant growth. Furthermore, B. licheniformis inhibited fungal growth as revealed by ergosterol/chitin analysis. As shown by phospholipid fatty acid proﬁles, the inoculation caused a slight alteration in the microbial community structure of the rhizosphere, both in the total community and the culturable populations.
Keywords: ballota; microbial community structure; mycorrhiza; PGPR; quercus ilex ssp

Bacillus spp. and Pisolithus tinctorius effects on Quercus ilex ssp. ballota: a study on tree growth, rhizosphere community structure and mycorrhizal infection - Domenech, Jezabel; Ramos-Solano, Beatriz; Probanza, Agustin; Lucas-Garcı́a, José Antonio; Colón, Juan José; Gutiérrez-Mañero, Francisco Javier (Forest Ecology and Management, 2004)
A local species of oak (Quercus ilex ssp. ballota) was inoculated or co-inoculated with the ectomycorrhizal fungus Pisolithus tinctorius and two plant growth promoting rhizobacteria (PGPR) of the genus Bacillus (Bacillus licheniformis CECT 5106 and Bacillus pumilus CECT 5105). Effects of inoculation on growth, on N acquisition by the plant roots, changes in rhizosphere microbial communities and the degree of mycorrhization were evaluated. Only B. licheniformis promoted the growth of Q. ilex seedlings while co-inoculation of either bacterial strain with P. tinctorius had a negative effect on plant growth. Furthermore, B. licheniformis inhibited fungal growth as revealed by ergosterol/chitin analysis. As shown by phospholipid fatty acid proﬁles, the inoculation caused a slight alteration in the microbial community structure of the rhizosphere, both in the total community and the culturable populations.
Keywords: ballota; microbial community structure; mycorrhiza; PGPR; quercus ilex ssp